Ageing and Elderly Care in Kerala. (August 2020) - Rajan, S. Irudaya; Shajan, Aneeta; Sunitha, S.
This article presents an overview of the elderly in Kerala and describes various dimensions of elderly care and concerns, based on data from the Kerala Ageing Survey (KAS) 2013, conducted by the Centre for Development Studies (CDS), Thiruvananthapuram, Kerala. The article looks into the main issues, policies and programmes related to ageing and elderly care practices in Kerala and also addresses the basic care response at three levels: household, institutional and society. The ageing process in Kerala is witnessing an increase in the ratio of elderly population along with fundamental changes in families and communities. Hence, in order to accommodate the needs of the ageing population in society, various systems need to be reconstructed. The concerns and issues surrounding the ageing population requires long-term attentiveness and forward planning, where policies must be adopted with consideration for cultural and social contexts. Care for the elderly should focus on a holistic combination of health care, socio-economic protection and provision of a suitable environment for better quality of life.